Analisis Sebaran Oksigen Terlarut Dan Korelasinya Dengan Suhu Permukaan Laut Di Wilayah Pesisir Pulau Lusi Sidoarjo Menggunakan Citra Satelit Landsat-8 - Aditya Bagus Yoga; Hendrata Wibisana; Siti Zainab (Racic : Rab Construction Research, 2025)
Indonesia has an area of around 1,904,569km² with the largest archipelago in the world, namely 17,508 islands. One example of an island formed from sediment is in Sidoarjo Regency, East Java Province due to the Lapindo mud phenomenon from 2006 until now. Over the years, the overflowing mud was directed into the Porong River and settled, resulting in Lusi Island. The government is trying to plant mangroves and the result is that mangroves can grow well on this sedimentary island so that Lusi Island is used as a tourist attraction in Sidoarjo Regency. The natural uniqueness of Lusi Island and its surroundings, including the coast of the island, can be maximized through science and technology. One of the technologies used is remote sensing from Landsat-8 satellite imagery, this technology is used to observe the entire surface of the earth. To get the best results, the system used is a mathematical algorithm. The results of this analysis will later be confirmed with field conditions. The aim of this research is to analyze the distribution of dissolved oxygen and sea surface temperature in the coastal area of Lusi Island. The analysis results show that the value of field data taken in November 2023 for dissolved oxygen is 3.27 mg/L - 7.17 mg/L and for sea surface temperature is 30.3°C - 34.2°C. Meanwhile, image data is 2.86 mg/L - 21.16 mg/L and sea surface temperature is 28°C - 34.2°C. The two field data have a fairly strong negative correlation value of -0.604533307.